Assembling actin filaments for protrusion. (February 2019) - Rottner, Klemens; Schaks, Matthias
Abstract : Cell migration entails a plethora of activities combining the productive exertion of protrusive and contractile forces to allow cells to push and squeeze themselves through cell clumps, interstitial tissues or tissue borders. All these activities require the generation and turnover of actin filaments that arrange into specific, subcellular structures. The most prominent structures mediating the protrusion at the leading edges of cells include lamellipodia and filopodia as well as plasma membrane blebs. Moreover, in cells migrating on planar substratum, mechanical support is being provided by an additional, more proximally located structure termed the lamella. Here, we systematically dissect the literature concerning the mechanisms driving actin filament nucleation and elongation in the best-studied protrusive structure, the lamellipodium. Recent work has shed light on open questions in lamellipodium protrusion, including the relative contributions of nucleation versus elongation to the assembly of both individual filaments and the lamellipodial network as a whole. However, much remains to be learned concerning the specificity and relevance of individual factors, their cooperation and their site-specific functions relative to the importance of global actin monomer and filament homeostasis.